The Application of Deductive Method in Modeling Tourist Movement in Local Destinations - Sari Oktaviani, Putri (Jurnal Toursci, 2023)
This paper aims to develop a model of tourist movement in local destinations using the deductive method. The model is based on examining how intervening factors as determinants that have been identified previously in urban transport modeling and tourism literature can affect movement in local destinations. This study uses a literature study approach. This analysis aims to develop a model of tourist movement based on determinant factors that have been previously identified in the tourism literature. Data were analyzed using spatial analysis. The results of the study show that the model of tourist movement in local destinations consists of four main components, namely origin, destination, modes and routes. Intervening factors that influence tourist movements are sociodemographic characteristics, travel characteristics, destination characteristics, and external factors. This paper also discusses the implications and limitations of the model and suggests directions for future research.